Het conflict van de Westelijke Sahara: Een muur van zand en een muur van stilte - Cordier, Geert (Afrika Focus, 1986)
For more than a decade the Saharawi people have been fighting for their independence, first against the Spanish colonialists then against Morocco and Mauretania. Although Mauretania has withdrawn from the conflict, the POLISARIO-front, the liberation organisation of the Saharawi people, remains at war with Morocco. The Western Sahara, thus still forms a pole of tension in Northern Africa but the European Press does not pay it much attention. However committees to support the Saharawi people have been trying to break down this wall of silence. An "intergroupe de solidarité avec le peuple sahraoui", set up in the European parliament in May 1986, may constitute a major step towards mobilizing public opinion on the Saharawi case. This article, which gives a chronology of the conflict in its regional context, seeks to contribute to a better understanding of the problems of the Saharawi. KEYWORDS : liberation war, Morocco, occupation, POLISARIO, Western Sahara